Wrongful Convictions and Erroneous Acquittals: Applying Packer’s Model to Examine Public Perceptions of Judicial Errors in Australia - Williamson, Harley (International journal of offender therapy and comparative criminology, 2023)
The fallible nature of the criminal justice system continues to see judicial errors—that is, wrongful convictions and erroneous acquittals—undermine its integrity, efficacy, and legitimacy. Public perceptions of judicial errors are important contributors to criminal justice policy and reforms. The current study utilizes the 2016 Australian Survey of Social Attitudes (AuSSA) dataset to examine public attitudes toward judicial errors. It applies Herbert Packer’s crime control and due process models to understand how concerns around procedural safeguards and public safety are associated with public perceptions toward judicial errors. Packer’s model has been challenged by studies, which theorize that the models are not mutually exclusive. Yet, they have not been empirically tested in this context, which is a gap this study seeks to fill. Findings show that due process and crime control concerns shape public attitudes toward wrongful convictions and challenge the notion that Packer’s models be applied on a continuum.